2021
DOI: 10.1088/1361-6404/ac3f27
|View full text |Cite
|
Sign up to set email alerts
|

Variational approach to the Schrödinger equation with a delta-function potential

Abstract: We obtain accurate eigenvalues of the one-dimensional Schr\"{o}dinger equation with a Hamiltonian of the form $H_{g}=H+g\delta (x)$, where $\delta (x)$ is the Dirac delta function. We show that the well known Rayleigh-Ritz variational method is a suitable approach provided that the basis set takes into account the effect of the Dirac delta on the wavefunction. Present analysis may be suitable for an introductory course on quantum mechanics to illustrate the application of the Rayleigh-Ritz variational method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is shown that delta-function potential changes significantly the quantum harmonic oscillator spectral features [35,36]. However, the delta-function potential has often been viewed as an excitation introduced into the oscillator [37][38][39]. The variational method can be applied to investigation of the spectral features of the oscillator with the delta-function potential [40].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that delta-function potential changes significantly the quantum harmonic oscillator spectral features [35,36]. However, the delta-function potential has often been viewed as an excitation introduced into the oscillator [37][38][39]. The variational method can be applied to investigation of the spectral features of the oscillator with the delta-function potential [40].…”
Section: Introductionmentioning
confidence: 99%